Building a world class HR department. Issue 4 (13th August 2018) - Ulrich, Dave; Grochowski, Joe
Abstract : Purpose: This paper aims to define and clarify the nine criteria of an effective HR department, and it illustrates how these nine criteria deliver value across four distinct stages of an HR department. Design/methodology/approach: This research is based on over 100, 000 respondents from the HR competency study along with interviews and discussions with senior HR professionals in over 100 global 500 organizations across all industry sectors. Findings: Many HR transformation efforts exclusively focus on how to organize the HR department. This paper argues that organizing and designing the right HR department is an important part of HR transformation, but focusing only on the HR department is a narrow focus of the overall effectiveness of HR. The overall effectiveness of the HR department consists of nine criteria that deliver value across four stages. Originality/value: This paper provides HR professionals with a simple and practical framework to audit the overall effectiveness of the HR department by clarifying the nine criteria of an effective HR department that deliver value across four stages.